2011
DOI: 10.1159/000323971
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Eu- and Heterochromatin of <i>Citrus</i> with a Focus on the Condensation Behavior of 45S rDNA Chromatin

Abstract: To characterize the properties of eu- and heterochromatic regions in Citrus species, the chromosomal distribution of different histone H3 marks, DNA methylation sites (5mC) and 45S ribosomal DNA sites were determined for C. clementina, C. paradisi, C. sinensis, and for the hybrid Ortanique C. reticulata × C. sinensis. Our data show that in the relatively small genomes of investigated Citrus species (genome size ranges from 378–400 Mbp) the euchromatin is characterized by histone H3 lysine 4 mono-, di- and trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 70 publications
3
28
0
2
Order By: Relevance
“…Furthermore, Yamamoto et al [2009] reported a single pair of 5S rDNA sites in chromosomes of Citropsis gabunensis, Citrus reshni, Fortunella japonica, Clymenia polyandra and Swinglea glutinosa and in 3 pairs in Poncirus trifoliata , but they did not investigate the position of 45S rDNA. Likewise, the number of 45S rDNA sites was previously reported for several Citrus species [Kang et al, 2008;Marques et al, 2011] and some related genera [Barros e Silva et al, 2010]. However, simultaneous detection of 5S and 45S rDNA sites in the same cell was previously reported only for P. trifoliata and Citrus species of the subgenus Citrus [Pedrosa et al, 2000;Carvalho et al, 2005;Brasileiro-Vidal et al, 2007;Moraes et al, 2007a, b].…”
mentioning
confidence: 72%
“…Furthermore, Yamamoto et al [2009] reported a single pair of 5S rDNA sites in chromosomes of Citropsis gabunensis, Citrus reshni, Fortunella japonica, Clymenia polyandra and Swinglea glutinosa and in 3 pairs in Poncirus trifoliata , but they did not investigate the position of 45S rDNA. Likewise, the number of 45S rDNA sites was previously reported for several Citrus species [Kang et al, 2008;Marques et al, 2011] and some related genera [Barros e Silva et al, 2010]. However, simultaneous detection of 5S and 45S rDNA sites in the same cell was previously reported only for P. trifoliata and Citrus species of the subgenus Citrus [Pedrosa et al, 2000;Carvalho et al, 2005;Brasileiro-Vidal et al, 2007;Moraes et al, 2007a, b].…”
mentioning
confidence: 72%
“…The largest 45S rDNA site in Z. biebersteiniana , for example, was hypermethylated, while the smallest was hypomethylated [Cremonini et al, 2003]. In another example, the levels of methylation in 45S rDNA sites were directly related to the condensation states observed in different species of the genus Citrus , and uncondensed and hypomethylated sites were found to be related to active genes [Marques et al, 2011]. Different lineages of A. suecica , however, demonstrated large variation in methylated 45S rDNA sites [Pikaard, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that CMA + bands carrying 45S rDNA sites can be less bright or even neutral (Moraes et al 2007b) and may change the apparent size of the CMA + band at the microscopic level. Possibly, the epigenetic mechanisms involved in the regulation of the 45S rDNA expression (Pikaard 2000;Marques et al 2011) may influence the affinity of the CMA for its sequence.…”
Section: Discussionmentioning
confidence: 99%